Autoimmune glial fibrillary acidic protein astrocytopathy coexistent with reversible splenial lesion syndrome: A case report and literature review - Lin, Jing; Dong, Liangbin; Yu, Li; Huang, Jingwei (Frontiers in Neurology, 2023)
Autoimmune glial fibrillary acidic protein (GFAP) astrocytopathy is a rare autoimmune disorder. Reversible splenial lesion syndrome (RESLES) is a transient clinical-imaging syndrome characterized by specific magnetic resonance imaging (MRI) pattern. A 58-year-old man was admitted with a fever, headache, and confusion for 1 week. Brain MRI showed abnormal leptomeningeal enhancement in the brainstem and high signal intensity on diffusion-weighted MRI of the corpus callosum. Anti-GFAP antibody was positive in the serum and cerebrospinal fluid analysis. This patient significantly improved and had no relapse after glucocorticoid and immune suppressant therapy. A repeated brain MRI revealed the lesion in the corpus callosum and abnormal leptomeningeal enhancement in the brainstem disappeared. Linear perivascular radial enhancement is the characteristic pattern of autoimmune GFAP astrocytopathy which is rarely coexistent with RESLES.